2021
DOI: 10.1152/ajpcell.00454.2020
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8A homohexameric channels poorly recapitulate VRAC regulation and pharmacology

Abstract: Swelling-activated VRACs are heterohexameric channels comprising LRRC8A and at least one other LRRC8 paralog. Cryo-electron microscopy (EM) structures of non-native LRRC8A and LRRC8D homohexamers have been described. We demonstrate here that LRRC8A homohexamers poorly recapitulate VRAC functional properties. Unlike VRACs, LRRC8A channels heterologously expressed in Lrr8c-/- HCT116 cells are poorly activated by low intracellular ionic strength (µ) and insensitive to cell swelling with normal µ. Combining low µ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 48 publications
5
34
0
Order By: Relevance
“…Insight into the structural basis of VRAC modulation was obtained from cryo-EM structures of LRRC8A-sybody complexes. Irrespective of the fact that LRRC8A homomers are not found under physiological conditions, such assemblies form functional anion channels, although with compromised activation properties 18,23,24 . Moreover, the observed strong potentiation of LRRC8A activity by the sybodies Sb4 and Sb5 and its inhibition by Sb3 further emphasize an equivalent modulatory role of binders also in the context of homomeric channels (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insight into the structural basis of VRAC modulation was obtained from cryo-EM structures of LRRC8A-sybody complexes. Irrespective of the fact that LRRC8A homomers are not found under physiological conditions, such assemblies form functional anion channels, although with compromised activation properties 18,23,24 . Moreover, the observed strong potentiation of LRRC8A activity by the sybodies Sb4 and Sb5 and its inhibition by Sb3 further emphasize an equivalent modulatory role of binders also in the context of homomeric channels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The general architecture of LRRC8 channels was revealed from homomeric structures of the LRRC8A [18][19][20][21] and LRRC8D 22 subunits. Although such homomeric assemblies are not observed in a cellular context, the subunits form hexamers and, in case of LRRC8A, they function as ion channels with compromised activation properties 18,23,24 . With respect to their structure, homomeric LRRC8A channels appear to exhibit general features that are also observed in heteromeric proteins 18 .…”
mentioning
confidence: 99%
“… 38 Accumulating evidence from the structure of LRRC8A and other electrophysiological studies indicated that heteromeric channels comprising LRRC8A and at least one other LRRC8 paralog are crucial for VRAC activity. 37 , 38 , 39 , 40 However, some other studies show that LRRC8A is dispensable for VRAC activity, 15 , 16 suggesting that LRRC8A alone is not sufficient for volume regulation in response to hypotonic stimulation and VRAC activity in all cell types. The controversy of these studies led us to investigate whether LRRC8A is necessary for VRAC functions in cerebrovascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, the studies from two laboratories identified LRRC8A as an essential component of VRAC 13,14 . It has been demonstrated that LRRC8A homohexamers poorly recapitulated VRAC electrophysiological properties 38 . Accumulating evidence from the structure of LRRC8A and other electrophysiological studies indicated that heteromeric channels comprising LRRC8A and at least one other LRRC8 paralog are crucial for VRAC activity 37–40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation